Postures des soignants proposant une éducation thérapeutique du patient dans un service de rééducation réadaptation cardiovasculaire. - Michael Racodon; Philippe Masson (Éducation et Socialisation)
Therapeutic patient education (TPE) is an integral part of the management of cardiac patients in cardiac rehabilitation. During the last decade, the development of this education was a long and complex process that transformed the caregiver profession and changed its relationship with patients. Health professionals have had to revise their thinking and redirect their work to fill the conditions for quality education while applying the guidelines of supervisory authorities. The objective of this study is to examine paramedical therapeutic education and the different educational approaches of the caregivers, in order to improve professional practice and to promote patient’s observance. A reflexive analysis of the educational experience has been conducted with paramedical in of rehabilitation over the last ten years. We observed that the role of the caregiver has evolved since the introduction of therapeutic education and that new forms of relations appear with the patient. The medical staffs, by helping patients to change their lifestyle, have seen their roles evolve and so they have learned to adapt to this new therapeutic demand.